Extremely High Phosphate Sorption Capacity in Cu-Pb-Zn Mine Tailings. - Longbin Huang; Xiaofang Li; Tuan A H Nguyen (PLoS ONE, 2015)
Elevated inorganic phosphate (Pi) concentrations in pore water of amended tailings under direct revegetation may cause toxicity in some native woody species but not native forbs or herb species, all of which are key constituents in target native plant communities for phytostabilizing base metal mine tailings. As a result, Pi sorption capacity has been quantified by a conventional batch procedure in three types of base metal mine tailings sampled from two copper (Cu)-lead (Pb)-zinc (Zn) mines, as the basis for Pi-fertiliser addition. It was found that the Pi-sorption capacity in the tailings and local soil was extremely high, far higher than highly weathered agricultural soils in literature, but similar to those of volcanic ash soils. The Langmuir P-sorption maximum was up to 7.72, 4.12, 4.02 and 3.62 mg P g-1 tailings, in the fresh tailings of mixed Cu-Pb-Zn streams (MIMTD7), the weathered tailings of mixed Cu-Pb-Zn streams (MIMTD5), EHM-TD (fresh Cu-stream, high magnetite content) and local soil (weathered shale and schist), respectively. Physicochemical factors highly correlated with the high Pi-sorption in the tailings were fine particle distribution, oxalate and dithionite-citrate-bicarbonate extractable Fe (FeO and Fed), oxalate-extractable Al and Mn, and the levels of soluble Cd and Zn, and total S and Fe. Large amounts of amorphous Fe oxides and oxyhydroxides may have been formed from the oxidation of pyritic materials and redox cycles of Fe-minerals (such as pyrite (FeS2), ankerite (Ca(Fe Mg)(CO3)2 and siderite (FeCO3), as indicated by the extractable FeO values. The likely formation of sparingly soluble Zn-phosphate in the Pb-Zn tailings containing high levels of Zn (from sphalerite ((Zn,Fe)S, ZnS, (Zn,Cd)S)) may substantially lower soluble Zn levels in the tailings through high rates of Pi-fertiliser addition. As a result, the possibility of P-toxicity in native plant species caused by the addition of soluble phosphate fertilizers would be minimal.